Immune Infiltration of MMP14 in Pan Cancer and Its Prognostic Effect on Tumors - Li, Minde; Li, Shaoyang; Zhou, Lin; Yang, Le; Wu, Xiao; Tang, Bin; Xie, Shenhao; Fang, Linchun; Zheng, Suyue; Hong, Tao (Frontiers in Oncology, 2021)
Background: Matrix metallopeptidase 14(MMPL4) is a member of the matrix metalloproteinase family, which interacts with tissue metalloproteinase inhibitors (TIMPs), and is involved in normal physiological functions such as cell migration, invasion, metastasis, angiogenesis and proliferation, as well as tumor genesis and progression. However, there has been a lack of relevant reports on the effect of MMP14 on pan-cancer. This study aims to explore the correlation between MMP14 and pan-cancer prognosis, immune infiltration, and the effects of pan-cancer gene mismatch repair (MMR), microsatellite instability (MSI), tumor mutation load (TMB), DNA methylation, and immune checkpoint genes. Methods: In this study, we used bioinformatics to analyze data from multiple databases, including TCGA, Oncomine and Kaplan-Meier Plotter. We investigated the relationship between the expression of MMP14 in tumors and tumor prognosis, the relationship between MMP14 expression and tumor cell immune infiltration, and the relationship between MMR gene mismatch repair (MMR), microsatellite instability (MSI), tumor mutation load (TMB), DNA methylation, and immune checkpoint genes. Results: MMP14 expression is highly associated with prognosis of a variety of cancers, tumor immunoinvasion, and has important effects on pan-oncologic mismatch repair (MMR), microsatellite instability (MSI), tumor mutation load (TMB), DNA methylation, and immune checkpoint genes. Conclusion: MMP14 is highly correlated with tumor prognosis and immunoinvasion, and affects the occurrence and progression of many tumors. All these fully indicate that MMP14 may be a biomarker for the prognosis, diagnosis and treatment of many tumors, and provide a new idea and direction for subsequent tumor immune research and treatment strategies.